Effective meetings : 20 sure-fire tools - Parker, Glenn M., 1938- (Parker team series, 2009)
A successful meeting is not measured by starting on time, having a great agenda, getting everyone involved, or even serving healthy muffins. While all these factors are important…a great meeting is simply one that achieves its objectives—in other words, where a problem is solved, a decision is made, a plan is developed, a question answered, or some other specific outcome is accomplished. In Volume II of The Parker Team Series, Effective Meetings: 20 Sure-Fire Tools, author Glenn Parker will help you achieve your desired outcomes. This easy-to-read book will guarantee better meeting results, wh.